Memahami dan Mengenal Ciri-Ciri Keaslian Uang Rupiah Kertas Tahun Emisi 2022 Pada Anak-Anak - Marlissa, Elsyan Rienette; Tebay, Vince; Ohoiwutun, Yosephine; Poli, Agustina Ivonne; Aedah, Nur; Numberi, Gerdha Kristina Ivony; Sawen, Kristina; Asmarani, Nur (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2023)
This activity aims to provide education and knowledge about understanding and recognizing the characteristics of the authenticity of Rupiah banknotes for the 2022 emission year in the activities of the Sunday school children of the Kingmi Eklesia Angkasa Church, Jayapura City in carrying out family, congregational and state economic activities. The methods used are lectures, discussions and questions and answers. This activity was welcomed by the church and the Sunday school children of the Kingmi Eklesia Angkasa Church, Jayapura City, gained knowledge about how to recognize genuine payment instruments.